Nest Architecture Development of Grass-Cutting Ants, Atta capiguara (Hymenoptera: Formicidae) - Farias, Adriano Pimentel [UNESP] (2020)
Atta capiguara grass-cutting ants are commonly found in the Cerrado biome, in open fields. Although grass-cutting ants build giant nests, little has been elucidated about this building pattern and when chambers and tunnels emerge. The present study describes the nest architecture development of A. capiguara grass-cutting ants from data on 31 cement-molded nests. A. capiguara nests grow with increases in the number of fungus chambers and emergence and increase of waste chambers and foraging tunnels. The structural growth of A. capiguara nests in the first year and a half of age (18 months) is vertical, with the building of the first chambers in the soil profile. After 18 months, the nests grow sideways with the addition of chambers and tunnels, and the first waste chambers appear. Between 18 and 54 months, the number of fungus chambers increases from 1-3 to 21-32, and the chambers are concentrated at the soil surface, although they can be found more than 3 in deep. In addition, the total volume of the waste chambers increases with the increment in the fungus chambers volume. Thus, this study contributes to understanding the nest architecture development of A. capiguara grass-cutting ants and demonstrates that the total volume of waste chambers is proportional to the total volume of fungus chambers suitable for the colony.